Pelatihan Senam Hamil pada Ibu Hamil di RT03/RW01 Desa Labuhan Tangga Hilir Kecamatan Rokan Hilir - Herlina, Sara; Siagian, Dewi Sartika; Qomariah, Siti; Sartika, Wiwi; Ratih, Rini Hariani; liza, Nurma (UKInstitute, 2021)
During pregnancy, the mother experiences physical and psychological/emotional changes in the pregnant woman. During pregnancy, emotions easily fluctuate and rise, which occurs due to hormonal changes. As for the anxiety before childbirth, pregnant women will appear statements and images of whether they can give birth normally, how to push, whether something will happen during childbirth, or whether the baby is born safely, will increasingly appear in the mother's mind, this condition can cause further anxiety and tension to form a feedback cycle that can increase overall emotional intensity. To break the cycle of anxiety, pregnancy exercise as a prenatal service is an alternative therapy that can be given to pregnant women. The purpose of this service is to increase the knowledge of mothers and do structured pregnancy exercises. The method in this service is pregnancy exercise counselling and pregnancy exercise training. The result of this community service is that it is known that 60% of participants have a pretest score of less than 65 about pregnancy exercise and after an explanation, 80% of the participants get a score of more than 65. The results of pregnancy exercise training, the majority of mothers did pregnancy exercises at home and there was a reduction in low back and back pain as much as 66.6%. Conclusion: Based on the results of pregnancy exercise counselling, there was an increase in knowledge seen from the pre and post-test scores, namely from 40% to 80% and pregnant women also did pregnancy exercises at home and there was a reduction in pain as much as 66.6%. Abstrak: Selama kehamilan, ibu mengalami perubahan fisik dan kejiwaan/emosi ibu hamil. Pada masa kehamilan, emosi mudah turun dan naik, yang terjadi akibat perubahan hormon. Adapun kecemasan menjelang pesalinan ibu hamil akan muncul pernyataan dan bayangan apakah dapat melahirkan normal, cara mengejan, apakah akan terjadi sesuatu saat melahirkan, atau apakah bayi lahir selamat, akan semakin muncul dalam benak ibu, kondisi ini dapat menyebabkan kecemasan dan ketegangan lebih lanjut sehingga membentuk suatu siklus umpan balik yang dapat meningkatkan intensitas emosional secara keseluruhan. Untuk memutuskan siklus kecemasan tersebut, maka senam hamil sebagai salah satu pelayanan prenatal, merupakan suatu alternatif terapi yang dapat diberikan pada ibu hamil. Tujaun Pengabdian ini adalah untuk menambah pengetahuan ibu dan melakukan senam hamil yang terstruktur. Metode dalam pengabdian ini adalah ceramah senam hamil dan pelatihan senam hamil. Hasil pengabdian kepada masyarakat ini adalah diketahui bahwa 60% peserta memiliki nilai pretest kurang dari 65 tentang senam hamiln dan setelah dilakukan penjelasan sebanyak 80% peserta mendapatkan nilai lebih dari 65. Hasil pelatihan senam hamil mayoritas ibu melakukan senam hamil dirumah dan terjadi pengurangan nyeri pinggang dan punggung sebanyak 66,6%. Kesimpulan: Berdasarkan hasil penyuluhan senam hamil terjadi peningkatan pengetahuan dilihat dari nilai pre dan post tes yaitu dari 40% menjedi 80% dan ibu hamil juga melakukan senam hamil dirumah dan terjadi pengurangan nyeri sebanyak 66,6%.